ChemInform Abstract: Solvothermal Syntheses and Characterizations of Selenidostannate Salts of Transition Metal Complex Cations: Conformational Flexibility of the Lamellar [Sn3Se72‐]n Anion. Issue 22 (15th May 2015) - Lu, Jialin; Shen, Yali; Wang, Fang; Tang, Chunying; Zhang, Yong; Jia, Dingxian
Abstract: Compounds (IV), (V), and (VII) are solvothermally prepared and characterized by single crystal XRD and UV/VIS spectroscopy.